Zone specific trends in coral cover, genera and growth-forms in the World-Heritage listed Ningaloo Reef. (September 2020) - Thomson, Damian P.; Babcock, Russell C.; Haywood, Michael DE.; Vanderklift, Mathew A.; Pillans, Richard D.; Bessey, Cindy; Cresswell, Anna K.; Orr, Melanie; Boschetti, Fabio; Wilson, Shaun K.
Abstract: On coral reefs, changes in the cover and relative abundance of hard coral taxa often follow disturbance. Although the ecological responses of common coral taxa have been well documented, little is known about the ecological responses of uncommon coral taxa or of coral morphological groups across multiple adjacent reef zones. We used Multivariate Auto-Regressive State-Space modelling to assess the rate and direction of change of hard coral cover across a variety of coral genera, growth forms, and susceptibility to bleaching and physical damage covering multiple reef zones at northern Ningaloo Reef in Western Australia. Trends were assessed between 2007 and 2016, during which multiple episodic disturbances occurred including cyclones and a heatwave. We provide evidence of zone specific trends, not only in total hard coral cover, but also in taxonomic and morphological groups of corals at Ningaloo Reef. Declines in total coral cover on the reef flat corresponded with declines in fast growing corals, particularly Acropora . In contrast, total coral cover on the reef slope and inshore (lagoon) did not undergo significant change, despite divergent trajectories of individual genera. Importantly, we also show that changes in the composition of coral assemblages can be detected using a morphological based approach when changes are not evident using a taxonomic approach. Therefore, we recommend that future assessments of coral reef trends incorporate not just standard metrics such as total coral cover, but also metrics that provide for detailed descriptions of trends in common and uncommon taxa and morphological groups across multiple reef zones. Highlights: Changes in coral cover were documented across reef zones, for common and uncommon genera, over a period of 10 years. Total coral cover declined only on the reef flat, due largely to declines in the most common taxa, Acropora . Declines in uncommon genera ( Favites, Dipsastraea ) were also detected. Corals with high susceptibilities to physical damage and to coral bleaching only declined within inshore and reef flat zones. Changes in the composition of assemblages were most evident when using a morphological based approach.